2023
DOI: 10.1007/s00262-023-03375-w
|View full text |Cite
|
Sign up to set email alerts
|

Human γδ T cells induce CD8+ T cell antitumor responses via antigen-presenting effect through HSP90-MyD88-mediated activation of JNK

Abstract: Human Vγ9Vδ2 T cells have attracted considerable attention as novel alternative antigen-presenting cells (APCs) with the potential to replace dendritic cells in antitumor immunotherapy owing to their high proliferative capacity and low cost. However, the utility of γδ T cells as APCs to induce CD8+ T cell-mediated antitumor immune response, as well as the mechanism by which they perform APC functions, remains unexplored. In this study, we found that activated Vγ9Vδ2 T cells were capable of inducing robust CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Based on our analysis and research results, we speculated that IS1 subtype might exhibit an immune “hot” phenotype, associated with active immune cells, while IS2 subtype might represent an immune “cold” phenotype, characterized by fewer active immune cells. In the immune “hot” IS1 phenotype, there might be more anti-tumor immune cells, such as CD56 bright natural killer cells, central memory CD8 + T cells, and gamma-delta T cells, which typically exert a positive effect against tumor growth [ [41] , [42] , [43] ]. Conversely, the immune “cold” IS2 phenotype might be more inclined to contain immune cells that promote tumor development, such as Th17 cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our analysis and research results, we speculated that IS1 subtype might exhibit an immune “hot” phenotype, associated with active immune cells, while IS2 subtype might represent an immune “cold” phenotype, characterized by fewer active immune cells. In the immune “hot” IS1 phenotype, there might be more anti-tumor immune cells, such as CD56 bright natural killer cells, central memory CD8 + T cells, and gamma-delta T cells, which typically exert a positive effect against tumor growth [ [41] , [42] , [43] ]. Conversely, the immune “cold” IS2 phenotype might be more inclined to contain immune cells that promote tumor development, such as Th17 cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, no significant differences were observed in the macrophage infiltration levels between the high-risk and low-risk groups, indicating that macrophage seems to influence limited in the progression of osteosarcoma. Notably, CD8 T cells, crucial for effective recognition and killing of tumor cells during the immune response ( 73 , 74 ), were observed to have lower infiltration levels in high-risk osteosarcoma patients compared to those at low risk ( Figure 8D ). This suggests that the sphingolipid-cuproptosis metabolic network participates in the recruitment of CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2019 ). Wang et al discovered that Vγ9Vδ2 T cell activation enhanced the ability of CD8 + T cells to counter osteosarcoma, with CD8 + T cells managing osteosarcoma progression through the direct elimination of tumor cells ( Wang S. et al, 2023 ). Wang et al also observed that elevated PLOD2 expression in osteosarcoma was associated with enhanced CD8 + T cell infiltration, with such infiltration contributing positively to tumor suppression ( Wang Z. et al, 2022 ).…”
Section: Immune Cellsmentioning
confidence: 99%
“…Treatments based on γδ T cells and NK cells also showed therapeutic potential. Wang et al’s findings indicated that human Vγ9Vδ2 T cells, as antigen-presenting cells, hold potential in osteosarcoma treatment; their activation increased CCL5 secretion through the upregulation of HSP90 production, MyD88, and JNK activation, effectively enhancing CD8 + T cell responses against osteosarcoma cells ( Wang S. et al, 2023 ). A further study indicated that decitabine, a demethylating agent, amplified the expression of NKG2D ligands including MICB and ULBP1 on osteosarcoma cell surfaces, thus rendering them more susceptible to γδ T cell attack.…”
Section: Osteosarcoma Treatmentmentioning
confidence: 99%